The Effect of Tempeh gembus on Malondialdehyde and Superoxide Dismutase Enzyme Levels in Rats with Diet-Induced Metabolic Syndrome - Pristina Adi Rachmawati; Diana Nur Afifah; Ninik Rustanti; Gemala Anjani; Ahmad Zulfa Juniarto (Faculty of Medicine, Universitas Diponegoro, 2022)
Background: High level of malondialdehyde (MDA) and low level of superoxide dismutase (SOD) are markers of oxidative stress and indicate enhance metabolic syndrome. Tempeh gembus is a food that has antioxidant properties which can decreased MDA concentration and increased SOD enzyme activity.Objective: The aim of this research was to determine the effect of Tempeh gembus on plasma MDA and serum SOD enzyme levels in metabolic syndrome rats.Methods: A post-test only experimental design was used in which 25 Sprague Dawley rats were divided into 5 equal groups of 2 control groups (K- and K+) and 3 treatment groups (P1, P2, P3). Metabolic syndrome was induced in the K+ control and the 3 treatment groups. Tempeh gembus were given for 4 weeks with the doses of 2.5g (P1), 5g (P2), and 7.5g (P3). Plasma MDA levels were measured by the Thiobarbituric Acid Reactive Substance (TBARS) method and serum SOD enzyme levels were measured by the Enzyme Linked Immunosorbent Assay (ELISA) method. The statistical analysis used One Way Anova test.Results: Tempeh gembus significantly decreased plasma MDA levels of metabolic syndrome rats (P=0.000) but had no significant effect on serum SOD enzyme levels in each treatment group (P=0.449).Conclusion: The dose of 7.5g Tempeh gembus was the most effective dose in reducing the plasma MDA level. Tempeh gembus in the 3 treatment doses significantly decreased plasma MDA levels but had no significant effect on serum SOD enzyme levels.